Terorisme Sebagai Extraordinary Crime Dalam Perspektif Hukum Internasional - Febby Nurfadilla; Raesha Diva Sugihharti; Nabila Destami; Anggita Shaina Octova (Jurnal Ilmiah Wahana Pendidikan, 2023)
The writing of this research was conducted to determine the role of international law in overcoming terrorism which is included in one part of special crimes and is included in the form of extraordinary crimes, because these crimes are not the same as criminal acts in general. As we know, terrorism begins to threaten various nations. Thus, in its eradication it is necessary to deal with the perspective of international law because this crime does not only threaten individuals but poses a threat to state sovereignty. Therefore, terrorism crimes that can be classified as crimes against humanity should be considered as international crimes. This study uses the normative legal research method by examining a statutory regulation that applies to a particular legal issue